Role of Cardiac Imaging in the Diagnosis of Immune Checkpoints Inhibitors Related Myocarditis - Ederhy, Stéphane; Salem, Joe-Elie; Dercle, Laurent; Hasan, Abrar Saqif; Chauvet-Droit, Marion; Nhan, Pascal; Ammari, Samy; Pinna, Bruno; Redheuil, Alban; Boussouar, Samia; Champiat, Stephane; Soulat-Dufour, Laurie; et al. (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICI) have constituted a paradigm shift in the management of patients with cancer. Their administration is associated with a new spectrum of immune-related toxicities that can affect any organ. In patients treated with ICI, cardiovascular toxicities, particularly myocarditis, occur with a low incidence (< 1%) but with a high fatality rate (30−50%).. ICI-related myocarditis has been attributed to an immune infiltration comprising T-cells positive for CD3+, CD4+, CD8+, and macrophages positive for CD68. The diagnosis remains challenging and is made based on clinical syndrome, an electrocardiogram (ECG), biomarker data, and imaging criteria. In most clinical scenarios, endomyocardial biopsy plays a pivotal role in diagnosis, while cardiac magnetic resonance imaging (cMRI) has limitations that should be acknowledged. In this review, we discuss medical imaging's role in optimizing the management of ICI related myocarditis, including diagnosis, prognostication, and treatment decision